2009
DOI: 10.1080/15622970902929876
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbidity of bipolar disorder in children and adolescents with attention deficit/hyperactivity disorder (ADHD) in an outpatient Turkish sample

Abstract: This study aimed to assess the prevalence of bipolar disorder (BPD) in children and adolescents with attention deficit hyperactivity disorder (ADHD), and to compare the clinical characteristics of a group with ADHD with a group with co-morbidity of ADHD and BPD. The study includes 121 individuals, aged 6-16 years, with a diagnosis of ADHD. Co-morbidity of BPD was evaluated using the Schedule for Affective Disorders and Schizophrenia for School-age Children-Present and Lifetime version (K-SADS-PL) and the Paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…Similar findings were reported by Lus and Mukaddes (2009) who found that 8.3% of a sample of 121 youth 6–16 years with ADHD also met diagnostic criteria for bipolar disorder and that those affected with this comorbidity had significantly more pathological scores on multiple CBCL scales and on the YMRS than other ADHD youth without this comorbidity. Bernardi et al (2010) identified a rate of co-occurrence of ADHD with bipolar disorder of 18% lifetime and 10% current in a sample of 100 adult bipolar outpatients aged 18–30 years.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings were reported by Lus and Mukaddes (2009) who found that 8.3% of a sample of 121 youth 6–16 years with ADHD also met diagnostic criteria for bipolar disorder and that those affected with this comorbidity had significantly more pathological scores on multiple CBCL scales and on the YMRS than other ADHD youth without this comorbidity. Bernardi et al (2010) identified a rate of co-occurrence of ADHD with bipolar disorder of 18% lifetime and 10% current in a sample of 100 adult bipolar outpatients aged 18–30 years.…”
Section: Introductionsupporting
confidence: 86%
“…A bidirectional and robust comorbidity between pediatric bipolar (BP)-I disorder and attention deficit hyperactivity (ADHD) has been well documented in pediatric and adult studies in both clinical and epidemiological samples (Biederman et al 2001; Kessler et al 2006; Singh et al 2006; Lus & Mukaddes 2009; Arnold et al 2011). Arnold et al (2011) examined the comorbidity between ADHD and bipolar spectrum disorders (BPSDs) in the Longitudinal Assessment of Manic Symptoms (LAMS) study.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly elevated rates of bipolar I disorder have also been reported in studies of youths with ADHD (12)(13)(14)(15), and this comorbidity has been confirmed in studies of adults with bipolar disorder and ADHD. Sachs et al (16) found significant ADHD comorbidity in adults with an onset of bipolar I disorder before age 19, but not for those with older ages at onset.…”
Section: Discussionmentioning
confidence: 70%
“…As our pooled analysis of the Massachusetts General Hospital data sets showed, this prediction was rejected. Moreover, if ADHD and bipolar I are a unitary disorder, then rates of comorbidity should be the same regardless of whether they are estimated from samples ascertained for ADHD or bipolar I disorder, yet the rates are much higher for the latter method of ascertainment (11)(12)(13)(14)29). Finally, the idea that the two disorders are the same suggests that the treatments of the two disorders would be the same, which is not the case (25,73,74).…”
Section: Discussionmentioning
confidence: 93%
“…Notably there is a huge research database in the industrialized countries that assists in the development of good quality health care services for children and adolescents [5][6][7][8][9][10]. Most of the studies reported externalizing disorders such as attention deficit hyperactivity disorder (ADHD) as the most common, followed by internal disorders such as depression and anxiety plus co-occurrence of internal and external disorders [11][12][13][14][15][16]. Overall childhood psychopathology is the harbinger of similar (homotypic) or dissimilar (heterotypic) adult psychopathology.…”
Section: Introductionmentioning
confidence: 99%